EBÛ TÂLİB'İN İMÂNINA DAİR SÜNNÎ BİR BAKIŞ: İBNÜ'L-MUZAFFER ER-RÂZÎ ÖRNEĞİ. - TAŞBAŞI, Adem (Dinbilimleri Journal)
The main focus of the article is the faith status of Abu Talib, the uncle and protector of Prophet Muhammad, with a particular emphasis on the critical and methodological approach of Ibn al-Muzaffar al-Razi, one of the prominent scholars of Ahl al-Sunnah. Ibn al-Muzaffar highlights that the widespread reports claiming Abu Talib died in disbelief are evaluated without considering chronological inconsistencies, weaknesses in the chains of transmission, and the sociological context; he argues that Abu Talib may have possessed a hidden faith in light of his unwavering support for the Prophet and the expressions found in his poetry. Furthermore, by revealing the historical and textual contradictions in attributing certain Qur’anic verses to Abu Talib, he states that definitive judgments can only be made based on conclusive evidence. The study shows that Abu Talib’s belief is defended not only in Shia thought but also within Ahl al-Sunnah literature, advocating for a historical and contextual evaluation free from sectarian biases. In conclusion, it is emphasized that the issue of Abu Talib’s faith should be approached with caution and from a scientific perspective, avoiding definitive judgments.